AB0775 A Model Osteoarthritis Consultation within Primary Care: A Novel Nurse-Led Approach to Promote Self-Management. (10th June 2014) - Healey, E.L.; Main, C.J.; Ryan, S.; McHugh, G.A.; Finney, A.; Dziedzic, K.S.
Abstract : Background: Osteoarthritis (OA) management is not seen as high priority for primary care and health professionals find management of OA challenging. The NICE (2008, 2014) and EULAR recommendations (2013) for OA stress the benefits of core non-pharmacological treatments. The MOSAICS study is one of the first to develop an integrated approach for implementing these recommendations within primary care. Evidence suggests that practice nurses often provide self-management support for patients with chronic disease and therefore may be best placed to offer this approach. Objectives: To describe the uptake of core recommendations for OA by specially trained practice nurses within an OA clinic. Methods: A nurse-led OA consultation was developed and implemented for 6 months within 4 general practices in the North West Midlands, UK. Patients with a clinical diagnosis of OA made by the GP were referred to the nurse OA clinic. Core recommendations (comprising the provision of information, advice on exercise and physical activity, and weight management) were delivered by specially trained practice nurses (n=9) using a patient-centred approach which included goal setting and problem solving over four consultations. The consultation was supported by a OA guidebook specifically developed by patients and health professionals. To determine the content of the nurse consultation, data were collected through case report forms (CRFs) completed by the practice nurses after each appointment. Results: Over the implementation period 268 patients were seen by the practice nurses in the OA clinics. Mean age of patients was 68.3±11.5 years, 60.9% were female and 22% reported multi-site OA at the initial consultation. Of those who reported single site OA, the majority reported knee pain (54.9%) as the reason for consulting, while 12.9% reported hip pain, 7.6% reported hand pain and 2.7% reported foot pain. The first consultation lasted 28.9 (SD 7.7) minutes, the second 21.5 (SD 7.4), the third 20.9 (SD 7.6) and the fourth 19.9 (SD 8.3). Attendance at follow-up was 70.1% for a second consultation, 39.8% for a third and only 19.8% returned for a fourth. With regards to the uptake of the core treatments at the first consultation the nurses reported that they discussed the OA guidebook with the majority of patients (94.8%). Joint specific exercise and general physical activity were also advised and discussed with 89.6% and 88.1% of patients, respectively. Weight management was discussed with 74.6% of patients. By the fourth consultation the use of the OA guidebook reduced significantly (31.4%), despite the nurses being encouraged to use it as a key resource over the four consultations. Exercise, physical activity and weight management remained a consistent focus at the follow-up consultations. Conclusions: The data indicate that joint specific exercise and general physical activity were the major focus of the consultations. The majority of patients received the OA guidebook but it was not re-visited consistently at follow-up. This "model OA consultation" approach was implemented in practice as part of a cluster trial, and it appears to increase the uptake of core OA recommendations by practice nurses. Whether this approach is feasible within primary care and improves patient uptake and clinical outcomes warrants further evaluation. Acknowledgements: This presentation presents independent research funded by the National Institute for Health Research (NIHR) under its Programme Grants for Applied Research Programme (Grant Reference Number: RP-PG-0407-10386.) The views expressed are those of the author(s) and not necessarily those of the NHS, the NIHR or the Department of Health. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3721